Simulation of Recovery of Aroma Compound from Aqueous Solutions by Batch Pervaporation Coupled with Permeate Decantation and Water Phase Recycle - Mujiburohman, Muhammad; Feng, Xianshe (Journal of Membrane and Separation Technology, 2017)
In this work, the dynamic (batch) models of recovery of low soluble aroma compounds from aqueous solutions by pervaporation coupled with permeate decantation and water phase recycle was derived and simulated. The model was run to simulate the pervaporation of propyl propionate-water separation using PEBA membrane. The effect of two parametric models (i.e. ratio of feed mass over membrane area (F0/Am) and the aroma solubility in water) on the aroma compound recovery was studied. As compared to the conventional pervaporation, the application of water phase recycle was known to be able to enhance the recovery of aroma compounds in various extents, depending on the operating time and aroma solubility. The larger membrane area used (or smaller (F0/Am)) did not affect the maximum aroma compound recovery, but only shortened the operating time. For the aroma solubility of 0.56, 1, and 5 wt.%, referring to the optimum operating time in the conventional mode, the extent of improvement in recovery can be around 7, 10 and 16%, respectively. The modified pervaporation process also offered another advantage that the process would not be strictly restricted by the operating time due to permanent increase in cumulative mass of aroma compound recovered in the product.